Effects of a static synchronous series compensator (SSSC) based on a soft switching 48-pulse PWM inverter on the power demand from the grid - Ustun, T.S.; Mekhilef, Saad (2010)
In this paper the effects of a Static Synchronous Series Compensator, which is constructed with a 48-pulse inverter, on the power demand from the grid are studied. Extensive simulation studies were carried out in the MATLAB simulation environment to observe the compensation achieved by the SSSC and its effects on the line voltage, line current, phase angle and real/reactive power. The designed device is simulated in a power system which is comprised of a three phase power source, a transmission line, line inductance and load. The system parameters such as line voltage, line current, reactive power Q and real power P transmissions are observed both when the SSSC is connected to and disconnected from the power system. The motivation for modeling a SSSC from a multi-pulse inverter is to enhance the voltage waveform of the device and this is observed in the total harmonic distortion (THD) analysis performed at the end of the paper. According to the results, the power flow and phase angle can be controlled successfully by the new device through voltage injection. Finally a THD analysis is performed to see the harmonics content. The effect on the quality of the line voltage and current is acceptable according to international standards.